Frequency of Intestinal Tuberculosis Among the Cases of Intestinal Perforation Presenting at Ayub Teaching Hospital - Ullah, Aziz; Khaghan, Babar Sultan; Amin, Nadia; Rafique, Kashif (Biological and Clinical Sciences Research Journal, 2025)
Intestinal tuberculosis (ITB) remains a diagnostic challenge due to its nonspecific presentation and overlap with other abdominal pathologies. Among patients presenting with intestinal perforation, recognizing ITB is essential for prompt treatment, especially in regions with high tuberculosis prevalence. Objective: To evaluate the frequency of intestinal tuberculosis (ITB) among patients presenting with intestinal perforation and to explore its association with comorbid conditions such as malnutrition and cirrhosis. Methods: A cross-sectional study was conducted from January 2023 to December 2024, involving 157 patients diagnosed with intestinal perforation based on computed tomography (CT) findings at a tertiary care hospital. Patients aged 18 to 75 years of either gender were included. All patients underwent laparotomy, and tissue specimens from perforation sites were collected for histopathological evaluation to confirm ITB. Demographic and clinical data were recorded, including nutritional status and comorbid liver disease. Data were analyzed using SPSS version 25. Categorical variables were expressed as percentages, and associations were evaluated using the chi-square test with a significance level set at p < 0.05. Results: Among the 157 patients, 57.3% were male. Histopathological analysis confirmed ITB in 9.6% of cases. A statistically significant association was observed between ITB and cirrhosis (26.7%, p = 0.01) as well as malnutrition (53.3%, p = 0.002), suggesting these comorbidities may be risk factors for ITB-related intestinal perforation. Conclusion: Although infrequent, intestinal tuberculosis accounts for a notable proportion of intestinal perforations. The findings highlight the need for heightened clinical suspicion and early histopathological evaluation, especially in malnourished patients and those with cirrhosis, to improve diagnostic accuracy and clinical outcomes.